Blue Economy and Resilient Development: Natural Resources, Shipping, People, and Environment - Gao, Tianming; Erokhin, Vasilii; Zaikov, Konstantin; Vasile, Andrei Jean; Subić, Jonel (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book is a pivotal publication that seeks to address contemporary challenges to the blue economy in view of the growth in exploration and utilization of natural resources, transport connectivity, effects of climate change, sustainable fisheries management, food security, and social and economic issues of human well-being in coastal areas. Coastal territories and water areas are changing at an unprecedented pace in ways that fundamentally affect ecosystems, people, biodiversity, and sustainability. Such changes are driven primarily by rapid social and economic developments, economic disparities between countries, the internationalization of production and value chains, and industrialization. In this context, this publication supplements the existing literature by summoning political, economic, environmental, and social factors that influence various dimensions of the sustainable development of blue economy, as well as translating the findings into workable approaches and policies for the benefit of the economic actors, people, and the environment.